De gatos, ratones y caracoles. Continuidad y ruptura de las imágenes cinematográficas de la sociedad colombiana - Sonia Sánchez-Rivera (Les Cahiers ALHIM)
This article proposes a comparative analysis of the images of Colombian society configured in the films La estrategia del Caracol (Cabrera 1993) and Como el gato y el ratón (Triana 2002). It is assumed that the films are social testimonies that reveal unpublished areas of the world they shape (Casetti, 2005). The study focuses on the political significance of the tapes and their resonance in the construction of diverse images of Colombian society, as a reference of the Latin American universe. Based on a methodology that establishes the reading of works, in key to film theories (Casetti, 2005), conceptual and visual metaphors (Lakoff & Johnson, 2017) and some approaches to decolonial thinking (Quijano, 2000) is expected to show how cinema offers arguments, points of view or social, political and symbolic explanations that intervene in the creation of images of societies, their contexts and their history. The analysis of the films will allow to deepen the political status of the seventh art (Soulez, 2013), its ability to communicate and build representations, as well as to circulate other views of the Latin American.